Pengaruh Kualitas Pelayanan, Citra Merek dan Kualitas Produk Terhadap Loyalitas Konsumen Melalui Kepuasan Konsumen - Agus Agus; Siti Mujanah; Achmad Yanu Alif Fianto (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2024)
Brand image is one that triggers consumer loyalty to a product. This research investigates the influence of service quality, brand image and product quality on consumer satisfaction. Also investigate whether consumer satisfaction is a good mediator. This study conducted a survey of Selis electric motorbike users in Manokwari City. Using a purposive sampling method with the sample criteria being Selis electric motorbike owners, 152 respondents were obtained. The data was then analyzed using Structural Equation Modeling. The findings show that service quality and brand image make a positive contribution to consumer satisfaction. While product quality does not. Research also proves that consumer satisfaction mediates the relationship between service quality, brand image and product quality on tourist consumer loyalty. This study contributes to understanding marketing management by using the framework of consumer satisfaction and consumer loyalty in electric motorbike companies, which can also be applied to other general companies